2013
DOI: 10.1016/j.pbb.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptor 5 within nucleus accumbens shell modulates environment-elicited cocaine conditioning expression

Abstract: The metabotropic glutamate receptors 5 (mGluRs5) within the Nucleus Accumbens (NAc) have been implicated in the modulation of psychostimulant reward. We hypothesized that blockade of mGluR5 within the NAc shell would impair cocaine conditioning in rats. For this study, animals were implanted with cannulae within the NAc shell, and separate groups were exposed to a multimodal environment within activity chambers that signaled cocaine (cocaine-paired) or saline (controls, cocaine-unpaired) injections. Prior to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…In the present study, we found that systemic or local administration of MPEP into the NAc significantly inhibits cocaine self-administration under FR2 and/or PR reinforcement schedules, oral sucrose self-administration under PR reinforcement, as well as cocaine-induced reinstatement of drug-seeking behaviors. This is consistent with previous reports that pretreatment with MPEP or other mGluR5 antagonists (MTEP, fenobam, MFZ 10-7) inhibit cocaine self-administration 1 , 3 , 4 , 6 9 or cocaine-induced reinstatement of drug-seeking behavior 7 11 , 34 , 35 . Surprisingly, MPEP, at the same or higher doses, neither altered oral sucrose self-administration under FR2 reinforcement nor reinstatement of cocaine-seeking behavior triggered by cocaine-associated cues or footshock stress.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found that systemic or local administration of MPEP into the NAc significantly inhibits cocaine self-administration under FR2 and/or PR reinforcement schedules, oral sucrose self-administration under PR reinforcement, as well as cocaine-induced reinstatement of drug-seeking behaviors. This is consistent with previous reports that pretreatment with MPEP or other mGluR5 antagonists (MTEP, fenobam, MFZ 10-7) inhibit cocaine self-administration 1 , 3 , 4 , 6 9 or cocaine-induced reinstatement of drug-seeking behavior 7 11 , 34 , 35 . Surprisingly, MPEP, at the same or higher doses, neither altered oral sucrose self-administration under FR2 reinforcement nor reinstatement of cocaine-seeking behavior triggered by cocaine-associated cues or footshock stress.…”
Section: Discussionsupporting
confidence: 93%
“…In line with an interpretation of an extinction deficit is the exaggerated conditioned hyperactivity when mGlu5-deficient mice are returned (drug-free) to an environment previously paired with cocaine (Bird et al, 2010), suggesting a possible role for mGlu5 signalling in the integration of contextual information related to drug action. In agreement with this hypothesis, a recent study showed that intra-accumbal (shell) injection of MPEP acutely prior to a test session reduced conditioned hyperactivity (Martinez-Rivera et al, 2013), again implying a role for mGlu5 signalling in the learning process for association of environment/context and drug action.…”
Section: Mglu5 Receptors and Cocaine-driven Behaviorsmentioning
confidence: 56%
“…Importantly, infusion of MTEP into the NAcore had no effect on cue-induced sucrose seeking (Sinclair et al, 2012), making blockade of postsynaptic mGluR5 a more attractive pharmacological approach for preventing drug seeking than the activation of presynaptic mGluR2/3 receptors (Olive, 2009). Infusion of the mGluR5 antagonist MPEP, directly into the NAshell, also reduces cocaine contextinduced locomotion (Martínez-Rivera et al, 2013) as well as cocaine-primed reinstatement of cocaine seeking (Kumaresan et al, 2009). However, it is important to note that although MPEP and MTEP are both mGluR5 antagonists, studies show that MPEP may inhibit NMDARs to a certain extent, whereas MTEP has fewer off-target effects and is more selective for mGluR5 than mGluR1 compared with MPEP (Lea and Faden, 2006).…”
Section: Group I Metabotropic Glutamate Receptors (Metabotropic Glmentioning
confidence: 99%